Multiple Sclerosis: A Disease of Affluence? - Buchter, B.; Dunkel, M.; Li, Jianghong (S Karger AG, 2012)
Background: Multiple sclerosis is rare in tropical areas, but quite common in developed countries. Hence, latitude has been accepted as a causal factor for prevalence of multiple sclerosis. However, developed countries have also strong economic power, which may be measured by real gross domestic product per capita. Methods: Bivariate and multivariate regression models were used to assess the association of the prevalence of multiple sclerosis of 62 countries with real gross domestic product per capita and latitude. Results: Real gross domestic product per capita and latitude are positively associated with the prevalence of multiple sclerosis. Real gross domestic product per capita is a much stronger predictor of prevalence of multiple sclerosis than latitude. Conclusion: The strong correlation between the real gross domestic product per capita and the prevalence rates of multiple sclerosis is pointing to a new direction in research on the causes of multiple sclerosis. It is plausible that certain lifestyles and consumption behaviors that require high purchasing power might be associated with an increased risk of multiple sclerosis.